The optimization of learning in the university through its architecture: planning, human scale and living community - Pablo CAMPOS CALVO-SOTELO (Ediciones Universidad de Salamanca, 2018)
Higher education, channelized through teaching & learning processes, is a necessary spatial experience; this conviction constitutes the essential theoretical foundation which supports the present article. With the intention of optimizing motivation of students towards their formation, it becomes transcendental to combine three of the principles of the Educational Campus paradigm: spatial planning, human scale and existential communities of learning & research. Through the planning process, universities can draw long term evolution of their places, paying special attention to those characterized by their human scale. With such a sound strategy, students will increase their feeling of belonging towards the Institution, building up easily true communities of learning & research. With all these topics in mind, the purpose of the present text is to remark for the future the need of conceiving higher education spaces inspired on the concept of Educational Campus, which respond from innovation and sensitiveness to the contemporary situation and trends, enriching both the motivation of its users towards formation as well as its transcendental social projection.